PS-BPB04-8: ANGIOTENSIN II FORMULATIONS AND THEIR IMPACT ON CARDAIC, VASCULAR AND INFLAMMATORY MECHANISMS OF HYPERTENSION. (January 2023) - Nosalski, Ryszard; Booth, Emma; Saju, Blessy; Alsheikh, Eman; Crespo, Eva; Maffia, Pasquale; Graham, Delyth; Guzik, Tomasz
Abstract : Angiotensin II (AngII) is a major effector of the renin-angiotensin system, with a critical role in BP regulation of vascular function, and end-organ damage. AngII infusion, using osmotic minipumps, is the most common animal model of hypertension, recapitulating key vascular and cardiac features of human hypertension. While different formulations of AngII are available, their impact on the key outcomes of the model remains unknown. Accordingly, we compared two most commonly used AngII formulations, and their impact on the key cardiovascular endpoints in a mouse model of hypertension. Male 12-week old C57BL/6J mice (n = 11–14) underwent Sham, AngII[Val5] or AngII[Ile5] (490 ng/min/kg) treatment for two weeks, using osmotic minipumps. Blood pressure was measured by tail-cuff, vascular function by wire myography, remodelling by picrosirius red staining, mRNA expression using real-time PCR and perivascular (PVAT) inflammation by flow cytometry. Data were analyzed using one-way or RM-two-way ANOVA. Both AngII formulations caused a significant BP elevation (p < 0.001) in comparison to sham animals, although AngII[Val5] had a more pronounced pressure effect than AngII[Ile5] (171 ± 4 vs 156 ± 6 mmHg, p = 0.03). Similarly, endothelium-dependent relaxation of resistance arteries and aorta was significantly impaired by AngII infusion (p < 0.001), however, a maximum Ach-induced relaxation was significantly lower in AngII[Val5] than in AngII[Ile5]. Both, AngII formulations increased intima-media thickness of the aorta (p < 0.0001), although the effect of AngII[Val5] was ∼2-fold higher than AngII[Ile5] (p = 0.001). While animals infused with AngII[Val5] had enhanced vascular collagen deposition (p < 0.001), this effect was lesser in the AngII[Ile5] group (p = 0.02). The total number of leukocytes infiltrating PVAT was induced by both AngII formulations, however, this effect was less pronounced in AngII[Ile5] (1002 ± 376 vs. 753 ± 242 cell/mg, p = 0.03). The same effect was found among CD11b+ and CD11c+ cells. While a significant increase of CD3+ cells was observed in both AngII formulations. While cardiac hypertrophy was evident in both AngII formulations this effect was significantly lower in AngII[Ile5] (p = 0.03). This was confirmed by cross-sectional area of cardiomyocytes. Histological analysis of heart sections showed a significant effect of both AngII formulation on cardiac fibrosis (p < 0.05). This effect was more pronounced upon AngII[Val5] infusion (p < 0.001) and was associated with higher expression of pro-fibrotic markers. AngII[Val5] formulation is a more efficient and consistent way to study key cardiovascular endpoints such as BP, inflammation, vascular and cardiac damage compared with AngII[Ile5]. Furthermore, the use of AngII[Val5] leads to a more pronounced phenotype and may be associated with reducing the number of animals needed in experiments.